Toward Peace-Loving Attitude Trough Education Character - Dalmeri, Dalmeri; Gea, Antonius Atosokhi (Al-Ulum, 2015)
Efforts to solve violence had been faced by multi treatments. Violence in education is action over the standar of ethic and rule in education, either physically or disturbing the rights of ones. The actors can be anyone, Â including the chief of school, teacher, staff , student, parents and even society. Violence in education is assumed as effect of certain condition. Externally or internally, and it might happen with any trigger. This paper aims to analyse the importance of character building through peace-loving attitude to revitalize the actors of education as evaluation of structure and culture in the educational world. Our educational world recently sometimes shows its arrogancy and even militaristic behavior. While the basic tenet of education is to appreciate the understanding of human behavior in order to be enlighted and free.-----Upaya untuk menyelesaikan kekerasan pun menemui tantangan yang semakin kompleks. Kekerasan dalam pendidikan merupakan perilaku melampaui batas kode etik dan aturan dalam pendidikan, baik dalam bentuk fisik maupun pelecehan atas hak seseorang. Pelakunya bisa siapa saja: pimpinan sekolah, guru, staf, murid, orang tua atau wali murid, bahkan masyarakat. Kekerasan dalam pendidikan diasumsikan terjadi sebagai akibat kondisi tertentu yang melatar-belakanginya, baik faktor internal dan eksternal, dan tidak timbul secara begitu saja, melainkan dipicu oleh suatu kejadian. Tulisan ini menganalisa topik yang sangat penting untuk digali kembali oleh para insan pemerhati pendidikan sebagai wadah refleksi dan evaluasi kinerja struktural-kultural terhadap praksis dunia pendidikan. Dunia pendidikan yang akhir-akhir ini cenderung bernuansa arogansi intelektual atau bahkan bergaya militeristik yang tidak mengindahkan norma-norma etis. Padahal pendidikan seyogyanya memanusiakan manusia menuju taraf pemahaman yang lebih mencerahkan dan memerdekakan.